Prevalence of Noncommunicable Diseases' Risk Factors Among Secondary School Students in Eastern Iran in 2013 - Elaheh Yari; Amir Tiyuri; Davood Beheshti; Hooriyeh Khodabakhshi; Gholamreza Sharifzadeh (Shiraz University of Medical Sciences, 2016)
Background: Noncommunicable diseases (NCDs) are the main causes of mortality and disability in the world. In order for a campaign against NCDs' risk factors it is necessary to estimate the extent of their prevalence for their decrease through appropriate interventions. Objectives: The aim of this study was to determine the prevalence of NCDs' risk factors among secondary school students in Birjand city, east of Iran. Patients and Methods: In this cross-sectional study, 369 secondary school students aged between 15 - 20 years were selected using randomized cluster sampling in 2013. To gather data, the national health system questionnaire regarding NCDs with a stepwise approach was used. The data were derived by health trained workers through face-to-face interview, and physical assessments including height, weight, and blood pressure in every school. Finally, the obtained data were analyzed using the chi-square and Fisher's exact tests with the SPSS software version 18. Results: From a total of 369 students in the study, 180 cases (48.8%) were boys with the mean age of 16.98 ± 1.04 years. The prevalence rates of cigarette, and hookah smoking were 2.4% and 18.4%, respectively. Overweight and obesity were diagnosed in 15.2% of the population. The prevalence of hypertension was observed in 6% of the participants. The prevalence rates of hookah smoking and hypertension in boys were significantly higher than in girls (P < 0.05). Moreover, it was found that low consumption rates of fruits and vegetables were 57.7% and 58.3%, respectively. Conclusions: Generally speaking, the critical prevalence of NCDs' risk factors was observed. Regarding the more favorable effect of preventive measures on adolescents, planning for appropriate interventions to improve lifestyle to prevent various risk factors must be taken into account.